Structural and electrochemical studies of bromide derived ionic liquid-based gel polymer electrolyte for energy storage application. (December 2020) - Gupta, Ashish; Jain, Amrita; Tripathi, S.K.
Highlights: Ionic liquid based gel polymer electrolyte was synthesized, optimized and characterized by using bromide derived ionic liquid for energy storage applications. Morphological studies confirms the porous and predominantly amorphous nature of the prepared electrolyte material along with the good liquid retention capability which supports the electrical conductivity through its polymer matrix. The maximum room temperature ionic conductivity for the optimized system was found to be of the order of 2.05 × 10 −2 S cm −1 which is suitable for device fabrication point of view. The electrolyte films are suitable for supercapacitor application. Abstract: In the present studies, poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP), ionic liquid {1-Ethyl-3-methylimidazolium bromide} (EMIM)(Br), and magnesium perchlorate Mg(ClO4 )2 as salt were used to synthesize free standing electrolyte films by using solution cast technique. The prepared electrolyte films were investigated by using various structural and electrochemical techniques like scanning electron microscopy (SEM), X-ray diffraction analysis (XRD), Fourier transform infrared spectroscopy (FTIR) and differential scanning calorimetry (DSC) as well as ionic and temperature dependence studies. It has been observed that addition of ionic liquid significantly increases the properties like ionic conductivity, thermal stability, transparency etc. The maximum room temperature ionic conductivity for the optimized system was found to be of the order of 2.05 × 10 −2 S cm −1 which is suitable for device fabrication point of view. The optimized electrolyte films are suitable for supercapacitor application. Graphical abstract: Image, graphical abstract